Leedle Yawcob Strauss - Adams, Charles Follen, 1842-1918.
Autograph fair copy of "Leedle Yawcob Strauss," signed. Published in Leedle Yawcob Strauss and Other Poems (1878).
Poet.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Dialect poetry, German; Humorous poetry, American; Poets